Nilai-nilai Filosofis yang Terdapat pada Yoga Sutra Patanjali - Nurlaili M, Siti (Jurnal Filsafat "WISDOM", 2004)
Yoga Sutras of Patanjali is considered the defenitive work on traditional yoga, and is well known as the first ecer written. The Yoga Sutras of Patanjali dates back to around 1st and 3st century A.D. In this classic, Patanjali articulates the yogic cosmology through 195 Sutras (wisdom pearls). These sutras together form a tepestry of knowledge derived from many yogic traditions into a set of pity equations. According to the Yoga Sutras, the ultimate aim of Yoga is to reach "Kaivalya" (freedom). This experience of one's innermost being or "soul" (the Purusa). When this level of awareness is achieved. One becomes free the chains of cause and effect (Karma) which bound us to continual reincanation. Yoga Sutra of Patanjali discribes 8 discpline of yoga which must be practiced and refined in order to perciece the true self-the ultimate goal of yoga. He uses the term "Ashtanga Yoga" or the "eight limbs of Yoga".